Analysis of User Acceptance of the EPDesKel Application within the Nagari Government of Agam Regency Using the EUCS Method - La Ode Muhammad Rabil Saputra; Wa Ode Aulia Nurwansyah; Farid Ade Setiawan; Muhammad Rahimi Hasan; Wenty Zahrati; Ari Apriyansa (Jurnal Teknologi dan Komunikasi Pemerintahan, 2025)
The application EPDESKEL is a strategic information system designed for harmonizing the appraisal process of the performance in the village development fields. This research proposes efforts related to the analysis of determinant factors for acceptance and user satisfaction in the application among the Nagari Operators in Agam Regency using the End User Computing Satisfaction (EUCS) model. More specifically, this research is interested in investigating how five factors, namely content, accuracy, format, ease of use, and timeliness, affect end-user satisfaction as a whole. The research is done using a quantitative method involving saturated sampling, in which 92 operational end-users are involved as respondents. Structural Equation Modeling (SEM) analysis is conducted for this study, using Partial Least Squares (PLS). The conclusion drawn from this study shows that Ease of Use, Format, but not Content, Accuracy, nor Timeliness, are positive factors affecting user satisfaction positively. Implications of this study include the understanding that, in practice, user interfaces that are easy to interact with, rather than data accuracy, are viewed as even more essential factors in effective digital governance practices.   Keywords: Digital Governance, EUCS, Public Sector Technology, User Acceptance, Information System.